Longevity concept by regenerative medicine methods synergy: exosome therapy, functional medicine, and advanced multi-wavelengths laser therapy - Yasaman Zandi Mehran; Hans Michael Weber; Fateme Hoseinzade; Nahid Tafazoli Harandi; Mozhgan Ayazi; Shila Mirzadeh (European Journal of Translational Myology)
Regenerative medicine is one of the most important branches of medicine today and in the future and brings together all the methods to stop or even reverse the aging process. Regenerative medicine may include cellular therapies such as stem cell therapy or extracellular vesicle therapies such as exosomes and growth factor therapy. It may also involve the use of Photobiomodulation (PBM) and functional medicine treatments targets on mitochondrial medicine, to control the aging process. In this article, we have discussed the role, importance, rationale, overlap, and synergy of the joint application of these methods. Combining these regenerative medicine approaches can achieve better results in various medical indications. For longevity, any autoimmune disease, chronic disease, especially in elderly patients, this recommended combination seems to be very critical, for a higher survival rate in cell therapy methods. It is like a plant growing process that requires good quality seeds (cell therapy), light (targeted laser therapy) and good soil (functional medicine).